Oceanic high-frequency global seismic wave propagation with realistic bathymetry. Issue 2 (22nd May 2020) - Fernando, Benjamin; Leng, Kuangdai; Nissen-Meyer, Tarje
SUMMARY: We present a new approach to simulate high-frequency seismic wave propagation in and under the oceans. Based upon AxiSEM3D, this method supports a fluid ocean layer, with associated water-depth phases and seafloor topography (bathymetry). The computational efficiency and flexibility of this formulation means that high-frequency calculations may be carried out with relatively light computational loads. A validation of the fluid ocean implementation is shown, as is an evaluation of the oft-used ocean loading formulation, which we find breaks down at longer periods than was previously believed. An initial consideration of the effects of seafloor bathymetry on seismic wave propagation is also given, wherein we find that the surface waveforms are significantly modified in both amplitude and duration. When compared to observed data from isolated island stations in the Pacific, synthetics which include a global ocean and seafloor topography appear to more closely match the observed waveform features than synthetics generated from a model with topography on the solid surface alone. We envisage that such a method will be of use in understanding the new and exciting ocean-bottom and floating seismometer data sets now being regularly collected.